Penerapan Rendam Kaki Air Hangat terhadap Kualitas Tidur Pada Lansia di Wilayah Cantel Kulon Sragen - Putri Fatihah Cahyaningrum; Eska Dwi Prajayanti (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Elderly sleep disorders in Indonesia are quite high, namely 67%. Non-pharmacological treatment of sleep disorders can use warm water. Sleep disturbances have a negative impact, such as the elderly not being able to sleep at all at night and having nightmares. Warm water is able to provide relaxation which creates a feeling of comfort so that it can improve sleep quality. Objective : To determine the effect of soaking feet using warm water on the sleep quality of the elderly. Methods: The method used is descriptive with a pretest and posttest to 2 respondents in Cantel Kulon Sragen, the duration of soaking feet in warm water for 15 minutes with a water temperature of 40°C for 5 consecutive days on 25 May 2023-29 May 2023. Results : The sleep quality scores of the two respondents before the therapy were 12 and 10. After the therapy they were 7 and 6. Conclusion: Soaking feet in warm water for 15 minutes can improve sleep quality.